Community natural resource management and poverty in India : the evidence from Gujarat and Madhya Pradesh /: the evidence from Gujarat and Madhya Pradesh. (2016) - Enarth, Shashidharan; Enarth, Shashidharan; Pathak, Jharna; Shah, Amita, 1952-; Verma, Madhu; Wood, John R, 1940-
No abstract available